Google Docs 4 everyone - Holzner, Steven, 1957- (Que, 2009)
Google Docs gives millions of people all the office productivity software they need. Unlike the office suites it replaces, it's free, and completely online. This book covers all three of Google Docs' flagship applications, guiding you through all the common tasks you're likely to perform.